Antecedents of Green Consumption Attitudes and Consequences for Intentions and Buying Behavior of Non-Pesticide Vegetable and Fruit Products - KUSMANTINI, Titik; SUTIONO, Heru Tri; ASTUTI, Rini Dwi; EKAWATI, Terstina (Journal of Environmental Management and Tourism, 2021)
Research on the sustainability of consumption or consumption of green products has become the focus of academics and practitioners. The focus of the study is on the consumption of green products, especially agricultural products such as non-pesticide vegetables and fruits in Yogyakarta. To test the hypothesis using SEM (Structural Equation Modelling) Analysis bases on PLS (Partial Least Square) Technique. The data collection technique was carried out by distributing questionnaires to members of the green community or non-pesticide vegetables and fruit consumers in the many modern markets, and the sample size is 244 green consumers. The test results produce empirical evidence that the three antecedents of green consumption attitudes are proven to have a positive and significant effect, but the effectiveness of green consumption variable is the most dominant factor. The consequences of a better green consumption attitude have also been shown to have a significant effect on the buying intentions or behavior of green products. The practical implication of the results of this study is to provide input for research partners namely the Women Farmers Group (KWT) that is aiming at green product segments as an appropriate step in marketing their agricultural products. Effective marketing communication efforts need to be built through advertising and product packaging programs that are able to increase green trust.